CONDUCTIVITY AND DIELECTRIC PROPERTIES OF A NOVEL FERRITE ALLOY - Aziz K. Jahja; M. Silalahi; Tri Darwinto; Nurdin Effendi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
CONDUCTIVITY AND DIELECTRIC PROPERTIES OF A NOVEL FERRITE ALLOY. The synthesis of a new ferrite alloy with a composition of Fe (73.42 w%), Cr (18.0 w%), Si(1.0 w%), Mn(1.0 w%), C(0.08 w%) and Ti(6.5 w%) has been carried out. The frequency-dependent conductivity and dielectric response of this novel material have been investigated by RLC bridge impedance spectroscopy method. It was verified that the real dielectric constant e¢ of these new F-1 materials show different dielectric behavior with respect to Koops theory of dielectric response in standard ferrite materials. In the F-1 samples, no relaxation peaks are observed for the frequency range below 10 kHz, meaning low frequency behavior such as grain- boundaries effect and space charge polarization has not taken effect. Both dielectric response- and dielectric loss curves show frequency dispersive relaxation peaks, three regions of discontinuity and relaxation peaks were identified in the applied frequency range. The low frequencies up to 10 KHz, intermediate frequencies 10 kHz to 40 KHz, the dielectric constant tend to decrease forming a curve resembling a distorted quarter circle, and higher frequency-range > 40 kHz where a semicircle forms, centered around 60 kHz. Using Nyquist- and Bode plots, these relaxation processes are identified as (beginning of) formation of oxidation-layers at the surface because of sintering, electron transfers between cations and Maxwell-Wagner interfacial polarizations. It is concluded that this is a novel material with its own distinctive dielectric properties.